ANALISIS KOMPARATIF KINERJA KEUANGAN ALLIANZ LIFE INDONESIA DENGAN PT PRUDENTIAL LIFE ASSURANCE - chandra mandira, i made; dwija putri, igam asri (E-Jurnal Akuntansi, 2014)
The purpose of this study was to determine the financial performance and the average difference in the financial performance of insurance company Allianz Life Indonesia and PT. Prudential Life Assurance. This study used a different test independent (paired sample t-test). The results of analysis show that there are differences in average financial performance in the insurance company Allianz Life Indonesia and PT. Prudential Life Assurance. Risk Based Capital (RBC) Allianz Life Indonesia and PT. Prudential Life Assurance is healthy and safe for more than 120%. Security funds/technical reserves Allianz Life Indonesia and PT. Prudential Life Assurance has a graph that is increasing each year and can be considered healthy and safe. Gross premiums Allianz Life Indonesia and PT. Prudential Assurance from the 2009-2012 gross premium is increasing so the two companies can be categorized as healthy and safe. Net investment income/average investment Allianz Life Indonesia tend to formulate their investment portfolio in mutual funds and PT. Prudential Life Assurance in stock, though both these companies can be categorized as a healthy and safe.
Keywords: Risk Based Capital (RBC), security funds/technical reserves, gross premium/average equity, net investment income/average investment